Antioxidant Activity of Lactobacillus plantarum DY-1 Fermented Wheat Germ Extract and Its Influence on Lipid Oxidation and Texture Properties of Emulsified Sausages - Juan Wu; Yu Cheng; Ying Dong (Journal of Food Quality)
The nutrient compositions and in vitro antioxidant activities of water-soluble extract from Lactobacillus plantarum DY-1 fermented wheat germ and its effect on the lipid oxidation and texture properties of emulsified sausages were investigated. The optimal hydroxyl radical scavenging capacity of 72.8 ± 2.9% was demonstrated for fermented wheat germ extract (FWGE) by terms of the fermentation conditions as follows: fermentation time of 26 h, fermentation temperature of 35°C, initial pH of 3.0, solid to liquid ratio of 1/10, and inoculum amount of 0.48 g. The enhancement in FWGE content could improve the oxidation stability of emulsified sausages by retarding the formation of thiobarbituric acid-reactive substances (TBARSs) during 7 days of storage at 4°C. However, a higher FWGE content (2.14%) resulted in 78% of increase in cooking loss (p<0.05) and 41.4% of decrease in hardness (p<0.05) of emulsified sausages. It was suggested that the biotransformation of wheat germ with lactic acid bacteria could improve its nutritional quality and functional properties.